Factors of Consumer Behaviour of youth from middle-east when purchasing Organic Food (Global Scientific Review, 2022)
The objective of this paper is to analyse consumer behaviour (CB) of youths from middle-east for buying organic food. Our study brings information which can potentially be used for further research and will also be useful for organizations with a practical interest in the production sale and distribution of organic food. To investigate the influence of the various factors in CB, we have applied the Theory of Planned Behaviour (TPB) and Price Effect Theory (PET). In the current concept, there is no significant research conducted in measureing the factors of CB that influence youths in middle-east for organic food. The theoretical part deals with the concept of consumer behaviour, factors that affect the CB, and the conceptual framwork of TPB and PET. In the analytical part we have collected data from the sample of 200 potential consumers who are students in the various universtities in the metropolitan cities of three countries of middle-east, namely Kingdom of Saudi Arabia (KSA), United Arab Emirate (UAE) and Oman. Questionnaires are focused on measring the CB for purchasing organic food while following the theory of TPB and PET. Particular items were measured using a 6-point Likert´s scale, where 1 represented a negative attitude (completely disagree or definitely not) and 6 represented a positive attitude (completely agree or definitely yes). The authors opted for an even Likert scale in order to avoid the middle value and thus obtained the real opinion of the consumer who had to select one of the possibilities and thus adopt a position on the research issue. In the middle-east, the young consumer are influenced mainly by factors such as personal attitude and subjective norms. Limitations of this study are the fact that in our questionnaire we focused on how the consumer viewed the purchase of organic food in general and not how they view the purchase of individual organic. Our contribution is to identify the factors that influence youth‘s buying behaviour and choice for organic food in middle-east becuase their buying behaviour would help companies to innovate organic food and know the demand trends for the same.